Stylistica of Maulid Simtud Durar's Repetition Created by Habib Ali Bin Muhammad Husein Al-Habsyi - Huda, Nur; Sa'dudin, Ihsan (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
This study aims to describe the repetition and its effects in "Maulid Simtud Durar" by Habib Ali bin Muhammad Husein Al-Habsyi. This research is a qualitative study using descriptive methods. Qualitative research is one of the research procedures that analyzes descriptive data in the form of observed speech or writing. Descriptive method is aimed at describing and analyzing data about repetition language style in the maulid simtud durar. Repetition is a form of repetition, both in terms of sounds, syllables, or sentence parts that are considered important to put pressure in accordance with the expected context. This research confirms the existence of rhetorical language in the form of repetition contained and scattered in the maulid simtud durar to convey meaning and abstract thought then conveyed concretely through reps to give greater influence and effect in the hearts and minds of readers. The results of this study found six types of repetition, each of which was Tikrar Lafdzi (epanalepsis), Tikrar Taukidi (Epizueksis), Tajanus Sawti (Asonance), Mawjah Basitah (Simploke), Jinas Tam (Paranomasia), and Jinas Ghairu Tam. This research explains the ability of repetitive language styles in the maulid simtud durar to describe abstract meaning and thought, especially the emphasis on magical things and something amazing, whic the meaning is transformed into a repetition, because something that is visible and concrete can strengthen meaning and can have an effect that bigger in heart and mind.